1976
DOI: 10.2527/jas1976.4251227x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Patterns, Rectal Temperature, Serum Electrolytes and Packed Cell Volume in Beef Cattle Deprived of Feed and Water

Abstract: Two trials were conducted with a total of 12 beef heifers and steers to determine the effect of 48-hr deprivation of feed or water or both on rectal temperature, respiratory and heart rates, electrocardiograph (EKG) patterns, packed cell volume (PCV) and the concentrations of serum sodium, potassium, calcium and magnesium. The same measurements plus the serum concentration of total acid-soluble phosphorus were made in a third trial with six steers and a 96-hr deprivation period. A fourth trial was conducted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 10 publications
1
2
1
Order By: Relevance
“…Packed cell volume was greater (P < 0.001) in sick cows in comparison with cows that were not sick, which was likely a result of reduced water intake. Overall, these findings agree with other authors who observed no difference in mean PCV in water-deprived cattle (Rumsey and Bond, 1976;Cole and Hutcheson, 1981;Gortel et al, 1992;Bjerg et al, 2005).…”
Section: Resultssupporting
confidence: 93%
“…Packed cell volume was greater (P < 0.001) in sick cows in comparison with cows that were not sick, which was likely a result of reduced water intake. Overall, these findings agree with other authors who observed no difference in mean PCV in water-deprived cattle (Rumsey and Bond, 1976;Cole and Hutcheson, 1981;Gortel et al, 1992;Bjerg et al, 2005).…”
Section: Resultssupporting
confidence: 93%
“…However, as previously indicated no treatment effect on RT was resolved in the current study. In a previous study, RT decreased following 48 h deprivation of feed and water in steers; 14 in the current study CHRSUB and CHRINT had numerically reduced RT on d -3 compared to the other treatments that had not been restricted from water access at this time, but the difference was not statistically significant (P ~ 0.63).…”
Section: Rectal Temperaturecontrasting
confidence: 66%
“…Viremia was not detected. In all treatment groups, mean viral shedding reached a peak between days 2 and 4 after inoculation, declining thereafter with cessation of shedding by day 11 (Fig. 1).…”
Section: Experimental Excretion Of Ibr Virusmentioning
confidence: 88%